Rhetorical Structure of The News Story and Implication for Language Teaching - Sahan, Anselmus (International Journal of Language Education, 2020)
This study tried to investigate the application of the Rhetorical Structure Theory (RST) in analyzing the relationships between the markers used in the four texts and identify the types of the marker relationship and their functions in the whole clauses. It found out that RST operated with highly generalized Rhetorical Relations, such as elaboration, sequence, and motivation; it was intended to be applicable across a variety of different registers. Based on the analysis of texts 1-4, it was also found that the texts apply four types of elements of a clause complex covering elaboration, enhancement, projection, and extension. These findings are in line with the logical meaning which functions to realize its existence and application in some forms of news stories being analyzed. Therefore, teaching of Grammar and Writing Subjects should involve the process of discourse development and news stories so that students will enhance and update their knowledge and improve their understanding.Â